2019
DOI: 10.18632/oncotarget.26615
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced phosphatidylserine-selective cancer therapy with irradiation and SapC-DOPS nanovesicles

Abstract: Normal living cells exhibit phosphatidylserine (PS) primarily within the intracellular leaflet of the plasma membrane. In contrast, viable cancer cells have high levels of PS on the external surface, and exhibit a broad range of surface PS, even within specific types of cancer. Agents that target surface PS have recently been developed to treat tumors and are expected to be more effective with higher surface PS levels. In this context, we examined whether surface PS is increased with irradiation. In vitro irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 53 publications
(84 reference statements)
1
46
0
Order By: Relevance
“…Studies investigating the effects of irradiation on SapC-DOPS cytotoxicity have shown that fractionated radiation enhances the effect of SapC-DOPS in some cancer cell lines [23]. In vitro irradiation of cancer cell lines increased median surface PS expression of surviving cells [9]. The observed effects of increased surface PS and sensitization to SapC-DOPS was most pronounced in cell lines with lower initial surface PS expression.…”
Section: Sapc-dops Combination Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the effects of irradiation on SapC-DOPS cytotoxicity have shown that fractionated radiation enhances the effect of SapC-DOPS in some cancer cell lines [23]. In vitro irradiation of cancer cell lines increased median surface PS expression of surviving cells [9]. The observed effects of increased surface PS and sensitization to SapC-DOPS was most pronounced in cell lines with lower initial surface PS expression.…”
Section: Sapc-dops Combination Treatmentsmentioning
confidence: 99%
“…The unique appeal of SapC-DOPS as a cancer therapy include its consistent selective targeting and killing of cancer cells while being tolerated in healthy cellsthis phenomenon has been reflected in results of phase I clinical trials where SapC-DOPS showed a strong safety profile [24,25]. In addition, SapC-DOPS [1] utilizes multiple mechanisms to induce cancer cell death including caspase 9 cleavage and lysosomal membrane permeability [2] is capable of crossing the blood-brain tumor barrier and [3] enhances the effects of existing therapies [9,10,23,26]. Therapeutic assessment of SapC-DOPS and other PStargeting nanovesicles by other researchers indicate that, as a class, they are a promising therapeutic option for the treatment of several types of cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Everted PS is one consequence of caspase activation, but we have already noted, with respect to viruses, the inadequacies of exofacial PS as a suitable marker of irreversibly doomed targets. It is also less than ideal for marking CTL targets as irreversibly damaged, since it is upregulated on some infected cells that are appropriate targets, and on many viable tumor cells (9,16,20,66,67,95). Phagocytosis of infected or malignant cells expressing surface PS does induce local immune tolerance, and is an example of co-opted homeostatic effector down-modulation, but its indirect, cytokine-mediated mechanism of M2 induction makes it unsuitable as a contactdependent signal of target cell apoptotic status (9).…”
Section: Cytotoxic Lymphocyte Recognition and Avoidance Of Apoptotic mentioning
confidence: 99%
“…Investigators recently showed that initial HIV envreceptor engagement induces Ca++ flux-triggered PS externalization, which, in turn, dramatically enhances viral fusion and entry (16,95). In addition, many tumors upregulate surface PS (20), yet they remain susceptible-even preferentially so-to a variety of oncolytic viruses (66). PSmediated ''apoptotic mimicry'' refers to enveloped pathogens carrying everted PS exploiting cellular receptors for uptake of apoptotic debris, and indirect induction of interleukin (IL)-10 and other immunosuppressive cytokines by phagocytes after ingestion of infected cells or cancer cells exhibiting externalized PS (9).…”
mentioning
confidence: 99%